Oral microbiome correlates with selected clinical biomarkers in individuals with no significant systemic disease - Lim, Mi Young; Kim, Jung-Ha; Nam, Young-Do (Frontiers in Cellular and Infection Microbiology, 2023)
The oral microbiome is an important component of the microbiome in the human body. Although the association of the oral microbiome with various diseases, including periodontitis and cancer, has been reported, information on how the oral microbiome is related to health-related indicators in healthy populations is still insufficient. In this study, we examined the associations of the oral microbiome with 15 metabolic and 19 complete blood count (CBC)-based markers in 692 healthy Korean individuals. The richness of the oral microbiome was associated with four CBC markers and one metabolic marker. Compositional variation in the oral microbiome was significantly explained by four markers: fasting glucose, fasting insulin, white blood cell count, and total leukocyte count. Furthermore, we found that these biomarkers were associated with the relative abundances of numerous microbial genera, such as Treponema, TG5, and Tannerella. By identifying the relationship between the oral microbiome and clinical biomarkers in a healthy population, our study presents a direction for future studies on oral microbiome-based diagnosis and interventions.